2008
DOI: 10.1002/j.2050-0416.2008.tb00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and Fructose Fermentation by Wine Yeasts in Media Containing Structurally Complex Nitrogen Sources

Abstract: Glucose and fructose fermentations by industrial yeasts strains are strongly affected by both the structural complexity of the nitrogen source and the availability of oxygen. In this study two Saccharomyces cerevisiae industrial wine strains were grown, under shaken and static conditions, in a media containing either a) 20% (w/v) glucose, or b) 10% (w/v) fructose and 10% (w/v) glucose or c) 20% (w/v) fructose, all supplemented with nitrogen sources varying from a single ammonium salt (ammonium sulfate) to free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 32 publications
(64 reference statements)
2
3
0
Order By: Relevance
“…These results were in agreement with Zayed & Foley (1987) and El-Refai et al (1992) who found that the addition of urea significantly improved the ethanol yield. Junior et al (2008) found that peptone improved the fermentation performance of the yeast which was in agreement with the results obtained in this study. On the other hand, it was observed that ammonium sulphate was a good inorganic nitrogen source that stimulated the ethanol production.…”
Section: Discussionsupporting
confidence: 92%
“…These results were in agreement with Zayed & Foley (1987) and El-Refai et al (1992) who found that the addition of urea significantly improved the ethanol yield. Junior et al (2008) found that peptone improved the fermentation performance of the yeast which was in agreement with the results obtained in this study. On the other hand, it was observed that ammonium sulphate was a good inorganic nitrogen source that stimulated the ethanol production.…”
Section: Discussionsupporting
confidence: 92%
“…In addition an ordered utilisation was evident such that glucose was removed more rapidly than fructose. Similar reports of glucophilicity in industrial strains have been made by several authors [18,23,24,36,39]. Whilst the fermentation of a fructose medium was slower compared with an equivalent amount of mixed sugars, as reported recently [18], it is interesting that the relative strain performance in the former was not an eVective predictor of performance in the mixed sugar condition.…”
Section: Discussionsupporting
confidence: 59%
“…However, with the caveat that our study examined sugar utilisation rather than growth, the mismatch we observed between a glucose and fructose mixture and that of fructose alone (R 2 = 0.083) suggests it unlikely that a fructose-only medium will be useful to screen for performance in an extended mixed sugar fermentation. The presence of glucose is highly inXuential on fructose metabolism [14,18,19,21,27,28,32,37,38]. At this point it is not possible to state how glucose inXuenced fructose consumption.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In previous work, we have shown that, in general, the supplementation of the yeast growth media, containing sucrose, maltose, glucose or fructose, with a more complex structural nitrogen source such as peptone, induced higher biomass accumulation and ethanol production (5,(12)(13)(14). Studies with wine yeasts have also shown the effect of oxygen availability on a yeast's fermentation performance (5).…”
Section: Introductionmentioning
confidence: 95%